PROFILE OF METACOGNITION OF CLASS IX STUDENTS AT SMP NEGERI 19 PALU IN SOLVING STATISTICAL WORD PROBLEMS BASED ON COGNITIVE STYLES - Nurfadilah Nurfadilah; Alfisyahra Alfisyahra; Muh Hasbi; Mustamin Idris (FKIP Universitas Muhammadiyah Tangerang, 2026)
This study aims to describe the metacognition of students with cognitive styles of field independent and field dependent in solving statistical word problems. The research was conducted at SMP Negeri 19 Palu using a descriptive method with a qualitative approach. The subjects of this study were two students from Class IX B, consisting of one student with a field independent cognitive style and one student with a field dependent cognitive style, determined through the Group Embedded Figure Test (GEFT). The data collection techniques used in this study included a cognitive style test, a written test, and interviews, which were then analyzed using the Miles and Huberman model encompassing data condensation, data display, and conclusion drawing. The credibility test of the data employed in this study was participant validation (member check). The results of this study show that students with a field-independent cognitive style are able to fulfill all components of metacognition, which include regulation, planning, strategy, process, evaluation, and goals. Meanwhile, students with a field-dependent cognitive style are able to fulfill only some components of metacognition, which include regulation, planning, strategy, process, and goals.